The best age for learning a foreign language - Shevchenko, S. (My University, 2016)
When should we start to learn a foreign language? Nowadays children begin their acquaintance with foreign languages before starting school. Teenagers and young people are motivated to learn foreign languages for successful future. Adults know that English, for example, is very popular now. They realize that it is impossible to achieve a real success without foreign language. What age is the best for learning a foreign language? The author of the article had summarized the ideas of different specialists about this question. Different points of view and investigations about the best age of foreign language studying are considered in the article. Some examples of the paper are from the author’s professional background. The author describes the abilities, demands and problems of three age categories in learning a foreign language.
Keywords: foreign language